The spark factor : the secret to supercharging energy, becoming resilient, and feeling better than ever - Maloof, Molly, MD (Harper Wave, an imprint of HarperCollinsPublishers, 2023)
"Inside of you, there is a spark--it's what animates you, and without it, you could not live. This energy creation isn't mystical, nor is it spiritual; it is science. We know from research that our cellular machinery transforms the food we eat and the air we breathe into the electricity that fuels us. With the right lifestyle inputs, we glow with energy; but when the demands on our bodies exceed our capacity--as is true for so many of us--we become burned out, mentally and physically. Now, in The Spark Factor, Dr. Molly Maloof shares a program uniquely tailored to the biology of women--a plan that targets the mitochondria, the power source of the cells. As Dr. Maloof shows, the intense, all-or-nothing approaches commonly used by biohackers to optimize health--including sustained fasting, ultra-low-carb diets, and intense training--can be harmful, especially for women, because they create excessive stress in an already-stressed body, which can make us tired, weak, and prone to illness."--